Chemistry of Axial Filaments of Treponema zuelzerae - Bharier, M. A. (1971)
Highly purified axial filaments have been prepared from the spirochete Treponema zuelzerae, which possess a fine structure similar to the “beaded” form of bacterial flagella. The preparations consist largely of protein but also contain small amounts of hexose (less than 1%). The buoyant density of these filaments is 1.29 g/cm(3). At pH 4.3, in the presence of 4 m urea and 10(−3)m ethylenediaminetetraacetic acid, filament protein migrates as a single band in acrylamide gel electrophoresis. Filaments dissociate to subunits in acid, alkali, urea, guanidine or with heating, indicating that these subunits are not covalently bonded in the organized structure. This is consistent with amino acid analysis which reveals that, like bacterial flagella, the filaments are completely lacking in half-cystine. Sedimentation equilibrium measurements on dissociated axial filaments in 6 m guanidine show that the subunits are homogeneous with respect to molecular weight. A weight-average molecular weight of 37,000 ± 1,600 daltons is obtained from these measurements. The amino acid composition of axial filaments is similar to that of various types of flagellin molecules, but the filament protein is somewhat richer in tyrosine, phenylalanine, and proline than flagellin. Tryptic peptide maps of axial filaments are consistent with the amino acid composition calculated for a molecular weight of 37,000 daltons. No amino terminal end group could be detected by the dansyl chloride method, suggesting that this end group might be blocked in the axial filament protein. The results obtained show that the axial filaments of T. zuelzerae are similar chemically to bacterial flagella and suggest that they are composed of aggregates of a single species of protein subunit.